Teatro digital: uma experiência da Cia. Pierrot Lunar em “Antigamente, é quando?” - Neise Teixeira Neves (2023)
This dissertation aims to identify possible procedures for understanding, improving and systematizing the creation of so-called digital theater. It also seeks to point out its reverberations based on a literature review and on the analysis of "Antigamente, é quando?", an experience presented and broadcasted online in 2020 in Belo Horizonte by Cia. Pierrot Lunar, a theater collective whose member is the author of this study. Through a bibliographical review, a description of the procedures carried out in the creation and also gathering interviews with the team, categories of analysis were established with the intention of identifying elements that make up the work and finding ways to understanding how possible connections can be created between the artisanal character of theater, permeated by physical presence and its dialogues with the technology of remote transmission of presence. This phenomenon has been accentuated by the social isolation imposed by the Covid-19 pandemic and has brought new perspectives to theater. Finally, this study seeks to understand how the interference of digital media, permeated by cinema, audiovisual and the internet, can offer a plural look at the border relations between these languages.